The role of publication in the promotion of immunization programmes : a case study of Radio Uganda - Ojwe, Nahaman (Kampala : Makerere University, 1998)
Dissertation (Mass Comm.) - Makerere University, 1998.
Includes biliographical references (p.63-64)
Keywords: Immunisation of children -- Uganda; Radio in health education -- Uganda